2010
DOI: 10.1002/jmv.21919
|View full text |Cite
|
Sign up to set email alerts
|

Genetic characterization of bulgarian rotavirus isolates and detection of rotavirus variants: challenges for the rotavirus vaccine program?

Abstract: Objective Endothelial progenitor cells (EPCs) play an important role in tissue repairing and regeneration in ischemic organs, including the brain. However, the cause of EPC migration and the function of EPCs after ischemia are unclear. In this study, we demonstrated the effects of EPCs on ischemic brain injury in a mouse model of transient middle cerebral artery occlusion (tMCAO). Methods Circulating human EPCs were characterized with immunofluorescent staining and flow cytometry. EPCs (1 × 106) were injected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 75 publications
0
3
0
Order By: Relevance
“…These hospital-based studies performed between 2005 and 2008 reported that 28%-43% of the incidence of AGE and at least a third of all the hospitalizations of children less than five years old could be attributed to RV. 15,16 Overall, only 6.3% of the children in the study were hospitalized, 20.1% of the RVpositive and 1.5% of the RV-negative.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…These hospital-based studies performed between 2005 and 2008 reported that 28%-43% of the incidence of AGE and at least a third of all the hospitalizations of children less than five years old could be attributed to RV. 15,16 Overall, only 6.3% of the children in the study were hospitalized, 20.1% of the RVpositive and 1.5% of the RV-negative.…”
Section: Discussionmentioning
confidence: 97%
“…The existing incidence data for Bulgaria are based on hospitalized cases [15][16][17] but they include only the more severe cases and do not give an accurate impression of the epidemiology and actual burden of RV disease. By one estimate, up to one in five AGE cases will see a physician and no more than two percent will be admitted to a hospital or present to an emergency room while the remaining cases will be cared for in their home by the parents or other caregivers.…”
Section: Introductionmentioning
confidence: 99%
“…The dominant RV genotype has changed over the years: G4P [8] (40.6%) in 2005, G9P [8] (84.8%) in 2006, G2P [4] (45.1%) in 2007, GP1P [8] (39.5%) in 2008, and G4P [8] (47%) in 2009, although this has gradually been replaced by G2P [4] (27%) (18,19).…”
Section: Bulgariamentioning
confidence: 99%